2007
DOI: 10.1038/nbt1287
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial cells derived from human embryonic stem cells form durable blood vessels in vivo

Abstract: We describe the differentiation of human embryonic stem (hES) cells into endothelial cells using a scalable two-dimensional method that avoids an embryoid-body intermediate. After transplantation into severe combined immunodeficient (SCID) mice, the differentiated cells contributed to arborized blood vessels that integrated into the host circulatory system and served as blood conduits for 150 d.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
246
2
2

Year Published

2008
2008
2013
2013

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 273 publications
(260 citation statements)
references
References 13 publications
10
246
2
2
Order By: Relevance
“…Although various 3D culture systems (e.g., embryoid bodies) have been proposed for efficient generation of ECs (8), we found that a 2D approach is far more efficient than a 3D method for EC derivation from hESCs (20). However, the superiority of 2D culture was not known for iPS-EC differentiation.…”
Section: Discussionmentioning
confidence: 87%
See 4 more Smart Citations
“…Although various 3D culture systems (e.g., embryoid bodies) have been proposed for efficient generation of ECs (8), we found that a 2D approach is far more efficient than a 3D method for EC derivation from hESCs (20). However, the superiority of 2D culture was not known for iPS-EC differentiation.…”
Section: Discussionmentioning
confidence: 87%
“…We previously reported successful generation of durable engineered blood vessels in vivo using HUVECs (19) or ECs derived from cord blood-derived EPCs (26) or hESCs (20). In all cases, coimplantation with murine MPC 10T1/2 cells (19,20,26) or human MSCs (29) was required to sustain these engineered blood vessels in vivo. Translation of our previous findings will thus require patientcompatible sources of both ECs and mesenchymal cells in a large quantity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations